Pengembangan Materi Layanan Informasi Tentang Merokok - Husna Afdila; Rini Hayati (Journal on Education, 2024)
The author raises the issue the dangers smoking one of the Medan City Junior High School (SMP) environments. This research to develop information service materials about smoking. This research refers to research and development design or Research and Development subject of research, previous research sources quoted from Al Gafi (2019) Journal of Muara Sains, Technology, Medicine, Health Sciences. The object of research is the development of information service materials about smoking. The results of research and discussion of this research are media teaching module entitled the dangers of smoking which is interesting for students to used teaching media in schools. With this module, the material can be conveyed well and learning is more enjoyable. Development of media module for teaching the dangers of smoking with 4D module, namely: Define, including analysis of product needs, analysis of students, material concepts, learning objectives. Design aims to design learning products that have been determined. Development includes product revision from expert validation of teaching product feasibility and data collected in form learning media feasibility questionnaires by media experts, language experts and service experts Dissemination disseminating the product. Smoking information between students who received information about the dangers of smoking and those who did not.